2009
DOI: 10.2308/iace.2009.24.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Cost of an Accounting Education, Economic Returns, and Preparation to Enter the Profession

Abstract: Costs of a college education continue to increase faster than overall inflation. The debt students in the United States incur to complete college is also escalating. The purpose of this study is to examine the cost of obtaining an undergraduate and graduate degree in accounting and expected cash flows for the first ten years in public accounting for students with and without educational loans. We analyze CPA exam pass rates for any relationships between education costs and level of technical preparation for en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Donelan & Philipich (2001) surveyed CPA exam candidates and found that 57% had enrolled in a master's program while 43% obtained 150 hours with undergraduate credits. Studies have shown that pass rates are better for CPA candidates who have enrolled in masters programs (Menk, Nagle, & Rau, 2017, Dunn & Hooks, 2009. Booker, Hill, & Wright (2010) found students were more interested in completing 150 hours with undergraduate credits, preferably with a double major.…”
Section: Completing 150-hoursmentioning
confidence: 99%
“…Donelan & Philipich (2001) surveyed CPA exam candidates and found that 57% had enrolled in a master's program while 43% obtained 150 hours with undergraduate credits. Studies have shown that pass rates are better for CPA candidates who have enrolled in masters programs (Menk, Nagle, & Rau, 2017, Dunn & Hooks, 2009. Booker, Hill, & Wright (2010) found students were more interested in completing 150 hours with undergraduate credits, preferably with a double major.…”
Section: Completing 150-hoursmentioning
confidence: 99%
“…Descriptive statistics are presented. Dunn and Hooks (2009) explore the costs of an accounting education and the expected cash flow of 10 years in public accounting along with CPA exam pass rates. Significant detail is provided about universities with 40 or more students taking the CPA exam in 2006 (n = 279).…”
Section: Majormentioning
confidence: 99%